The role of virtual communities in promoting Electronic Commerce. - Koh, Yeow Leng. (2008)
In this paper we have looked at the issues of trust in virtual communities and the perceived benefits of participating in virtual communities. We have also outline a model that proposes the contributions of virtual communities to electronic commerce. The model was developed from an integration of relevant theories.